Hydrogen Production and Enzyme Activities in the Hyperthermophile Thermococcus paralvinellae Grown on Maltose, Tryptone, and Agricultural Waste - Hensley, Sarah A.; Moreira, Emily; Holden, James F. (Frontiers in Microbiology, 2016)
Thermococcus may be an important alternative source of H2 in the hot subseafloor in otherwise low H2 environments such as some hydrothermal vents and oil reservoirs. It may also be useful in industry for rapid agricultural waste treatment and concomitant H2 production. Thermococcus paralvinellae grown at 82°C without sulfur produced up to 5 mmol of H2 L−1 at rates of 5–36 fmol H2 cell−1 h−1 on 0.5% (wt vol−1) maltose, 0.5% (wt vol−1) tryptone, and 0.5% maltose + 0.05% tryptone media. Two potentially inhibiting conditions, the presence of 10 mM acetate and low pH (pH 5) in maltose-only medium, did not significantly affect growth or H2 production. Growth rates, H2 production rates, and cell yields based on H2 production were the same as those for Pyrococcus furiosus grown at 95°C on the same media for comparison. Acetate, butyrate, succinate, isovalerate, and formate were also detected as end products. After 100 h, T. paralvinellae produced up to 5 mmol of H2 L−1 of medium when grown on up to 70% (vol vol−1) waste milk from cows undergoing treatment for mastitis with the bacterial antibiotic Ceftiofur and from untreated cows. The amount of H2 produced by T. paralvinellae increased with increasing waste concentrations, but decreased in P. furiosus cultures supplemented with waste milk above 1% concentration. All mesophilic bacteria from the waste milk that grew on Luria Bertani, Sheep's Blood (selective for Staphylococcus, the typical cause of mastitis), and MacConkey (selective for Gram-negative enteric bacteria) agar plates were killed by heat during incubation at 82°C. Ceftiofur, which is heat labile, was below the detection limit following incubation at 82°C. T. paralvinellae also produced up to 6 mmol of H2 L−1 of medium when grown on 0.1–10% (wt vol−1) spent brewery grain while P. furiosus produced < 1 mmol of H2 L−1. Twelve of 13 enzyme activities in T. paralvinellae showed significant (p < 0.05) differences across six different growth conditions; however, methyl viologen-dependent membrane hydrogenase activity remained constant across all media types. The results demonstrate the potential of at least some Thermococcus species to produce H2 if protein and α-glucosides are present as substrates.